PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PERTUMBUHAN DAN PERKEMBANGAN MANUSIA BERBASIS GAMIFIKASI DI KELAS V SDN 4 ANGGREK KABUPATEN GORONTALO UTARA - Abdul Holik Kurniawan Wuwungan; Abdul Haris Panai; Irvin Novita Arifin; Gamar Abdullah; Rifda Mardian Arif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Abdul Holik Kurniawan Wuwungan, 2024. Development of Interactive Learning Media on Human Growth and Development Based on Gamification in Grade V at SDN 4 Anggrek, Gorontalo Utara Regency. The Principal Supervisor is Prof. Dr. Abdul Haris Panai, M.Pd., MCE., and The Co-Supervisor is Dr. Irvin Novita Arifin, S.Pd., M.Pd. This study aimed to (1) develop Interactive Learning Media on Human Growth and Development Based on Gamification in Grade V at SDN 4 Anggrek, Gorontalo Utara Regency, and (2) assess the feasibility and practicality of the Interactive Learning Media on Human Growth and Development Based on Gamification in Grade V at SDN 4 Anggrek, Gorontal Utara Regency. This study was conducted at SDN 4 Anggrek, Gorontalo Utara Regency, using the 4D model development approach. Data collection techniques included interviews, observations, and questionnaires. Moreover, the data were then analyzed using a Likert scale. The study resulted in a product in the form of interactive learning media based on gamification for human growth and development in grade V at SDN 4 Anggrek, Gorontalo Utara Regency. Feasibility tests conducted by experts yielded an average score of 90.7%, categorized as "Highly Feasible" However, the practicality tests yielded an average score of 92.4%, categorized as "Highly Practical." Thus, the Interactive Learning Media on Human Growth and Development Based on Gamification in Grade V at SDN 4 Anggrek, Gorontalo Utara Regency, developed by the researcher, is deemed feasible and practical for implementation.